Głosy z czasu Zagłady. Dwie relacje świadków z getta w Stanisławowie - Rachel Feldhay Brenner (Zagłada Żydów)
The author analyses two testimonies from the Stanisławów ghetto: Eliszewa/Elza Binder's and  Juliusz Feuerman's. Binder's diary, found in the ghetto, begins on 13 December 1941 and ends on 18 July 1942, whereas Feuerman's notes are a chronicle of the ghetto and the destruction of its inhabitants. the purpose of this analysis, supplemented by a biographical context, is to portray - as well as Brenner can - the characters of their authors. The reading of these two accounts, written in the same historical situation is to demonstrate that both the ideological and the emotional reactions to the current events in the ghetto ghetto cannot be separated from their personal emotional situation or their pre-war lives.